Labour market screening with intermediaries - Paul Schweinzer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We consider a Rothschild-Stiglitz-Spence labour market screening model and employ a centralised mechanism to coordinate the efficient matching of workers to firms. This mechanism can be thought of as operated by a recruitment agency, an employment office or head hunter. In a centralised descending-bid, multi-item procurement auction, workers submitwage-bids for each job and are assigned stable jobs as equilibrium outcome. We compare this outcome to independent, sequential hiring by firms and conclude that, in general, a stable assignment can only be implemented if firms coordinate to some extent.
urn:nbn:de:bvb:19-epub-13413-3
Keywords: C78; D44; E24; J41; 330; Matching; Multi-item auctions; Sequential auctions; Screening